The antecedent factor of tourists' intention to consume traditional food - Komariah, Kokom; Abdul Razzaq, Abdul Rasid; Nugraheni, Mutiara; Lastariwati, Badraningsih; Mahfud, Tuatul (2020)
Traditional food has become one of the essential aspects of developing culinary tourism. However, there are still limited studies that discuss the tourists' intention to consume traditional food when they tour. This study aims to reveal the antecedent factors of the intention to consume the traditional food of tourists when traveling. Data were randomly collected through an online questionnaire from local Malaysian and Indonesian tourists. Structural equation modelling (SEM) analysis is used to analyze the path between the antecedent factors forming the intention of tourists to consume traditional food. The results of the study show that attitude, subjective norms, and behavioural control factors are essential antecedents to form the intention of tourists to consume traditional food. Also, behavioural control is proven to be a primary mediator to strengthen the influence of attitude and subjective norms on the intention of tourists to consume traditional food during their trips. The results of this study have implications for tourism practitioners in developing new culinary tourism based on economic potential (traditional food).